Peningkatan kemampuan berbicara bahasa Prancis dengan menggunakan Jeux - Eviyanti, Evi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
The objective of this action research is to find out how to increase students’ speaking proficiency in French by using games. Games represent one of the teaching techniques that can be used in teaching Expression Orale II. This research was conducted at the French Language Study Program, Faculty of Language and Arts, State University of Medan. The participants of this research were students of the 2007/2008 academic year enrolled in Expression Orale II. The research method used was action research conducted in two cycles. The procedures of this action research were planning, acting, observing, reflecting, and replanning. The results indicate that after the actions in Cycles 1 and 2, students’ French speaking competence increased step by step. Based on the research, it can be concluded that the use of games in teaching Expression Orale II can improve students’ French speaking competence.